Implementasi pendidikan karakter melalui pembelajaran pendidikan Pancasila dan kewarganegaraan di sekolah berbasis pesantren - Lestari, Yuni Niki; Marzuki, Marzuki (Universitas Negeri Yogyakarta, 2020)
The purposes of this research are to describe the implementation of character education, identifying the affected factors and to analyze the right solution to solve the problem in the implementation of character education through the learning process of Civic and Pancasila Education for the students of Islamic boarding (pesantren) based school. This research is a descriptive qualitative research. The selection of the research subject is used by purposive technique. The data collection of the research is used by non-participant observation, interview and documentation. The validity of the research is used by triangulation. The data analysis process is based on the interactive model proposed by Miles and Huberman which include the data reduction, data display and drawing conclusion. The results showed that; (1) The implementation of character education through the learning process of Civic and Pancasila Education is through three phases namely plan, action and evaluation; (2) The supporting factors for character education include the boarding school environment of the islamic boarding school, the majority of teachers are alumni of the Islamic boarding school, and scout extracurriculer activity, while the inhibiting factors include the different characteristics of the santri, the distance between the santri male dormitory and the madrasah which is so far that the teacher cannot communicate directly, and the learning duration is small; (3) the possible solutions that will optimalize the learning results are the point system; when the students breaking the rules is 25 points as a warning and 50 points to reprimand the students, and the coordination and cooperation between madrasah and the boarding house.